Phytoplankton Diversity Effect on Ecosystem Functioning in a Coastal Upwelling System - Otero, Jaime; Álvarez-Salgado, Xosé Antón; Bode, Antonio (Frontiers in Marine Science, 2020)
Species composition plays a key role in ecosystem functioning. Theoretical, experimental and field studies show positive effects of biodiversity on ecosystem processes. However, this link can differ between taxonomic and functional diversity components and also across trophic levels. These relationships have been hardly studied in planktonic communities of coastal upwelling systems. Using a 28 yr time series of phytoplankton and zooplankton assemblages we examined the effects of phytoplankton diversity on resource use efficiency (RUE, ratio of biomass to limiting resource) at the two trophic levels in the Galician upwelling system (NW Iberian peninsula). Fitting Generalized Least Squares models we show that phytoplankton diversity was the best predictor for RUE across planktonic trophic levels. This link varied depending on the biodiversity component considered: while the effect of phytoplankton richness on RUE was positive for phytoplankton RUE and negative for zooplankton RUE, phytoplankton evenness effect was negative for phytoplankton RUE and positive for zooplankton RUE. Overall, taxonomic diversity had higher explanatory power than functional diversity, and variability in phytoplankton and zooplankton RUE decreased with increasing phytoplankton taxonomic diversity. Phytoplankton used resources more efficiently in warmer waters and at greater upwelling intensity although these effects were not as strong as those for biodiversity. These results suggest that phytoplankton species numbers in highly dynamic upwelling systems are important for maintaining the planktonic biomass production leading us to hypothesize the relevance of complementarity effects. However, we further postulate that a selection effect may operate also because assemblages with low evenness were dominated by diatoms with specific functional traits increasing their ability to exploit resources more efficiently.